Historical and Spiritual Manifestations of Mawlud Celebrations in The Republic of Kosovo - Hasani, Islam; Mehmeti, Sadik (Afkar: Jurnal Akidah dan Pemikiran Islam, 2025)
The spiritual heritage and ethno-cultural richness of Kosovo are both deep and diverse, manifested through various layers of tradition and practice. Among these is the long-standing tradition of celebrating Mawlud, the birthday of the Prophet Muhammad (PBUH). This practice, which has been present in the region for generations, is distinguished by unique characteristics and cultural expressions that hold significant value for the spiritual life of the Muslim community in Kosovo. The historical development, features, and specific forms of Mawlud celebrations, such as the recitation of poetry and singing about the life of the Prophet (PBUH), have played a vital role in preserving Islamic identity and transmitting religious teachings, particularly during the communist period when religious expression was restricted. This article analyses how Mawlud has been organised and celebrated, highlighting its importance in sustaining Islamic culture and community life. The research methodology is primarily based on empirical fieldwork and library research. Interviews were conducted with imams and elder community members who have witnessed or participated in Mawlud traditions. In addition to oral sources, the study draws upon published literature by reputable scholars and examines original vakifnames (or waqfiyyahs), some of the oldest surviving manuscript documents from the 16th century.